Analysis of Language Defense in Youtube Content Boy William National Examination (UNBW) - Shelvia Gusti Rahayu Pardede; Yusni Khairul Amri (Britain International for Academic Research (BIAR) Publisher, 2023)
Politeness is basically the speaker's way of communicating so that the speech partner does not feel pressured, cornered, or offended. Communication is a process that occurs in social life. At this time, almost all Indonesian people use social media and the biggest user is YouTube social media. Youtube is a social media that is watched by all people and all ages. Youtube contains various types of content, one of which is Boy William's YouTube channel entitled Boy William's National Examination (UNBW). This series discusses Youtube content for Boy William's National Examination (UNBW) with actresses Ayu Ting-Ting and Anwar. Politeness in language on Youtube social media functions to fence off Youtube users as polite loudspeakers. Conversations during UNBW will be the object of language politeness analysis with a review based on Leech's theory. The politeness theory put forward by Leech (1983: 132) is known as maxims which describe the realization of linguistic politeness, and further elaborates the linguistic politeness strategy into 6 maxims namely: 1) tact maxim, 2) generosity maxim , 3) approbation maxim, 4) modesty maxim, 5) agreement maxim, and 6) sympathy maxim. After reviewing the data, I pointed out that the conversation on UNBW's Youtube content for the Ayu vs Anwar series contains language that is impolite for other people to watch but is still considered polite if this conversation is only for Boy William, Ayu Ting-Ting, and just Anwar.